Genetic diversity, volatile constituents, cytotoxicity and genotoxicity of selected aromatic plant species from Ayer Hitam Forest Reserve - Jumaat, Siti Rahimah (2017)
Medicinal and aromatic plants (MAPs) are widely valued for their aromas, tastes, and remedies of various human illnesses. The Ayer Hitam Forest Reserve (AHFR) contains a high diversity of MAPs, which potential has not been explored. This study was conducted to assess the genetic diversity of MAPs at AHFR and to identify the chemical composition of several of them. Ten species of MAPs from eight families (Annonaceae, Asteraceae, Burseraceae, Lauraceae, Myrtaceae, Piperaceae, Rutaceae, and Thymelaeaceae) were collected based on morphological identification and subjected to DNA sequencing using the intergenic spacer region psbA-trnH and the nuclear ribosomal internal transcribed spacer 2 (ITS2). They were selected based on their medicinal and aromatic properties, which have been utilized by the aborigines at AHFR. DNA sequences of both regions had high similarities to their respective species in the Genbank. Phylogenetic trees were constructed and analyzed using Maximum Likelihood (ML) criteria together with 61 additional sequences of MAPs incorporated from the Genbank. Through molecular approach, species identity of these MAPs can be ascertained before employing their properties. The volatile constituents and toxicity content of three aromatic plant species, Syzygium polyanthum Wight (Walp.), Monocarpia marginalis (Scheff.) J. Sinclair, and Chromolaena odorata (L.) R.M. King & H. Rob, were determined, via Gas Chromatography (GC) with Flame Ionization Detector (FID). These species were chosen because of their distinct sensory characteristics with pleasant and strong odor of the leaves and stems. Altogether, 116 compounds were identified. Sesquiterpenes like α-cadinol, α-cedrene, cubenol, farnesol, ledol, trans-β-nerolidol, and γ-muurolene were abundantly found in both essential oils and crude extracts of three species. These genuine aromatic compounds display their potential on the significant properties primarily for fragrance and pharmaceutical purposes. To validate the safety consumption and application of these plant extracts, toxicity evaluations were carried out on human Peripheral Blood Mononuclear Cells (PBMCs). Three plant extracts were toxic to human PBMCs; the essential oils of M. marginalis and C. odorata, and hexane extract of C. odorata yielded IC50 and LD50 values of 76 mg/mL and 6,913 mg/kg, 14 mg/mL and 3,684 mg/kg, and 2.45 mg/mL and 1,927 mg/kg, respectively. The LD50 values indicated that the M. marginalis and C. odorata extracts were classified as slightly and moderately hazardous, respectively, for the oral and dermal hazardous levels according to the category of toxic chemicals set forth by the World Health Organization. A detailed toxicity evaluation via comet assay proved that all of the extracts of M. marginalis and C. odorata induced significant DNA damage (p < 0.05), while none of the S. polyanthum extracts exerted genotoxicity. Screening the phytochemical and toxicity contents of plants is crucial before their appropriateness for human consumption and application can be considered.